2022
DOI: 10.7883/yoken.jjid.2022.127
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genome Sequencing of Hepatitis E Virus Genotype 1 Imported from India to Japan

Abstract: Hepatitis E virus (HEV) is the causative agent of viral hepatitis E. In Japan, HEV genotype 3 (G3) and G4 are predominantly detected, while G1, mainly imported from countries in continental Asia, is rare. In the present study, we detected a G1 HEV strain in a patient who visited Japan from India. When PLC/PRF/5 cells (subclone 4-21) were inoculated with a stool suspension from this patient, accumulation of HEV RNA was observed in the spent culture medium, indicating that HEV had been successfully isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…One such strain that was derived from a patient who came to Japan from India was isolated, and a nearly complete HEV genome sequence has been reported for this isolate. 27 One of the limitations of the present study is that sequence data were obtained only from a subset of the reported cases. This shortcoming posed several challenges.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One such strain that was derived from a patient who came to Japan from India was isolated, and a nearly complete HEV genome sequence has been reported for this isolate. 27 One of the limitations of the present study is that sequence data were obtained only from a subset of the reported cases. This shortcoming posed several challenges.…”
Section: Discussionmentioning
confidence: 93%
“…Among the eight sequences categorized as G1, six sequences clustered with the reference sequence of G1g, and five of these six sequences were obtained from patients who appeared to have become infected in India. One such strain that was derived from a patient who came to Japan from India was isolated, and a nearly complete HEV genome sequence has been reported for this isolate 27 …”
Section: Discussionmentioning
confidence: 99%
“…� Travelers to endemic and developing countries should avoid drinking untreated water and eating raw food. 60,148,149 (A-1)…”
Section: Other Hepatitis E Vaccine Candidates and Their Status In Japanmentioning
confidence: 99%
“…Among the four major genotypes infecting humans, HEV-1 and genotype 2 HEV (HEV-2) are restricted to humans and have been responsible for multiple outbreaks in developing countries where the virus is transmitted through drinking contaminated water [18]. Although HEV-1 typically affects people in developing countries, such as South Asia and most countries in sub-Saharan Africa [19], imported infections have been reported in industrialized countries, including Japan [20][21][22]. HEV-1 infection in pregnant women frequently leads to infant mortality or premature delivery.…”
Section: Introductionmentioning
confidence: 99%